Characterisation of a novel laminarinase from Microbulbifer sp. ALW1 and the antioxidant activity of its hydrolysates. (9th May 2021) - Hu, Qingsong; Yin, Xiaoqian; Li, Hebin; Wang, Xinghua; Jiang, Zedong; Li, Lijun; Ni, Hui; Li, Qingbiao; Zhu, Yanbing
Abstract: Laminarin and its derived oligosaccharides have diverse bioactivities. The β‐1, 3‐glucanase in marine bacteria can be employed as a tool to digest laminarin in the cell wall of brown algae. Here, we cloned, expressed and characterised a β‐1, 3‐glucanase (laminarinase), MaLamNA, from the previously characterised marine bacterium Microbulbifer sp. ALW1, phylogenetically distinct from the glycoside hydrolase families of characterised laminarinases. The recombinant laminarinase was heterologously expressed and purified from Pichia pastoris GS115 cells with a molecular mass of 57.3 kDa. MaLamNA exerted its hydrolytic activity specifically against laminarin, with the highest activity at 45 °C and pH 4.5–5.5, respectively, and demonstrated high stability against extreme acidic and alkaline pH exposure. The addition of reducing agent dithiothreitol could significantly enhance the activity of MaLamNA. The hydrolytic products of laminarin by MaLamNA exhibited more effective antioxidant activities than the undigested laminarin. These characteristics of MaLamNA provide clues to its industrial application for laminarin bioresource development. Abstract : Novel laminarinase functions specifically toward β‐1, 3 linkages. The laminarinase demonstrates high stability against extreme acidic and alkaline pH exposure. The enzymatic hydrolysates of laminarin exhibit more effective antioxidant activities than the undigested laminarin.